The square [videorecording (DVD)] - Östlund, Ruben, 1974-; Moss, Elisabeth, 1982-; West, Dominic, 1969-; Notary, Terry (Magnolia Home Entertainment, 2018)
A satirical drama reflecting the times, about the sense of community, moral courage and the affluent person's need for egocentricity in an increasingly uncertain world.